2020
DOI: 10.7150/jca.46358
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic value of long non-coding RNAs in Colorectal Cancer: A systematic review and meta-analysis

Abstract: Background: Histopathological diagnosis remains the gold standard for the diagnosis of cancer, including colorectal cancer, but it is infeasible when tumor tissue is not available. With the recognition of long non-coding RNAs (lncRNAs), the expression of lncRNAs in serum or tissue samples has been reported as a diagnosis method for some cancers, however, the diagnostic value of lncRNAs for colorectal cancer remains unclear. Methods: A systematic review and meta-analysis were conducted. Eligible studies were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…With the rapid development of complex molecular biology techniques (e.g., qRT-PCR, in situ hybridization (ISH), RNA/DNA sequencing, NGS, and DNA methylation detection methods), there is a constant search for new biomarkers of cellular proliferation with potential diagnostic, prognostic, and/or predictive significance in cancers including CRC [ 115 , 236 , 259 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of complex molecular biology techniques (e.g., qRT-PCR, in situ hybridization (ISH), RNA/DNA sequencing, NGS, and DNA methylation detection methods), there is a constant search for new biomarkers of cellular proliferation with potential diagnostic, prognostic, and/or predictive significance in cancers including CRC [ 115 , 236 , 259 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
“…Non-coding RNAs most often show increased expression in CRC compared to the controls. Depending on what function a given ncRNA has in the tumor (oncogene, tumor suppressor), its overexpression or downregulation enhances proliferative activity and tumor progression [ 266 , 268 , 270 , 279 , 280 , 281 ].…”
Section: Methods To Assess Cell Proliferation In Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent technical advances have allowed the LncRNA field to make great progress, the list of LncRNAs and their potential association with diseases is expanding rapidly, and their relatively stable nature in the body fluids, ease of obtaining body fluids and detecting them using commonly used molecular biology techniques makes them attractive biomarker candidates ( 128 , 129 ). The results of a meta-analysis using data from over 1400 patients have shown that LncRNAs can serve as promising diagnostic biomarkers ( 130 ). For example, higher levels of LncRNA LIPCAR are associated with a higher risk of cardiovascular mortality ( 131 ), and LncRNA NONHSAT112178 can be a possible predictive biomarkers for coronary artery disease ( 132 ), Lnc HOTAIR is highly expressed in saliva samples of oral squamous cells from carcinoma patients, making it a strong candidate for metastatic oral cancer diagnosis ( 133 ), and Lnc MALAT1 is elevated in plasma and urine of prostate cancer patients ( 134 ).…”
Section: Long Noncoding Rnas As Biomarkers and Therapeutic Optionsmentioning
confidence: 99%
“…(Curcuma wenyujin Y.H. Chen & C.Ling) [16,17], has been widely used as an antitumor agent to treat a variety of tumors including lung cancer, liver cancer, digestive tract cancer, and bladder cancer, etc., even the patients with TKIresistant NSCLC can also benefit from the concurrent use of β-elemene with TKIs [18][19][20][21], however, the effects of β-elemene on TKI-resistant lung cancer and the underlying mechanisms of action are largely unknown. To address these issues, we investigated the effects of β-elemene on EGFR L858R/ T790M double mutation NCI-H1975 cells and the potential molecular mechanisms.…”
Section: Ivyspringmentioning
confidence: 99%